Thinking of Fish Population Discrimination: Population Average Phenotype vs. Population Phenotypes - Vasconcelos, Joana; Jurado-Ruzafa, Alba; Otero-Ferrer, José Luis; Lombarte, Antoni; Riera, Rodrigo; Tuset, Víctor M. (Frontiers in Marine Science, 2021)
The genetic polymorphism and phenotypic plasticity are key in ecology and evolution. The morphological variability of the contour of fish otoliths has been extensively used for the delimitation of stocks. These studies are conventionally based on average phenotype using elliptic Fourier analysis and lineal discriminant analysis as classifier. Considering new analytical options, such as the wavelet transform and non-parametric algorithms, we here analyzed the otolith shape of Trachurus picturatus from mainland Portugal, Madeira and the Canaries. We explore the phenotypic plasticity throughout a latitudinal gradient, establish a hypothesis to explain this plasticity based on the reaction norms, and determine how the use of average phenotype and/or morphotypes influences in the delimitation of stocks. Four morphotypes were identified in all regions, with an increase of phenotypes in warmer waters. The findings demonstrated that stocks were clearly separated with classification rates over 90%. The use of morphotypes, revealed seasonal variations in their frequencies and per region. The presence of shared phenotypes in different proportions among fishing grounds may open new management approaches in migratory species. These results show the importance of the phenotypic diversity in fisheries management.